Power Relations in Domestic Violence in West Lombok Regency - Titin Nurfatlah; Aryadi Almau Dudy; Suheflihusnaini Ashady; Zahratulain Taufik (Unram Law Review, 2024)
This research aims to examine cases of domestic violence in West Lombok Regency and explore the connection between power relations and domestic violence in the region. The research methodology employed is empirical legal research, utilizing several approaches, namely the statutory approach, the conceptual approach, and the sociological approach. The findings reveal that from 2023 to July 2024, there were 37 reported cases of domestic violence in West Lombok Regency. These cases include physical abuse, psychological abuse, sexual violence, and neglect within households. The victims are predominantly women, particularly wives, and children. The factors influencing the relationship between power dynamics and domestic violence include gender bias and the authority or power held within the household. In terms of power relations, husbands tend to exert high levels of conflict, control, and violence over their wives. The power wielded by the husband often oppresses members of the household, creating a power imbalance that adversely affects both wives and children. Furthermore, the patriarchal system, which grants husbands the authority to make all household decisions, exacerbates this imbalance. The power held by husbands often manifests in abusive behaviour, regardless of the family's economic standing. Even those with sufficient economic means and social status can engage in domestic violence, driven by the belief that, as the head of the family, the husband has the right to do so.